PERAN TALIBAN DALAM PRODUKSI OPIUM DI AFGHANISTAN TAHUN 2007 – 2011 - Lavina, Dicka Endri; Waluyo, Tri Joko (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This reasearch analyzes the role of Taliban in Opium trade in Afghanistan, especially during 2007 until 2011. Afghanistan is the world’s largest producer of opium. Since Taliban become the most powerful group in Afghanistan, Taliban is the one of most detrimental impact of opium poppy cultivation and opium trafficking in Afghanistan.Since the 2001 U.S. invasion of Afghanistan, the poppy trade has played a criticalmdestabilizing role, both in corrupting the Afghan government and police and in bankrolling the resurgence of the Taliban. This reasearch shows how Taliban commanders on the village level have expanded their activities related to drugs from collecting extortion and charging protection fees to running heroin refineries and other smuggling schemes.The datas were collected from many source like books, journals, and website that can support this reasearch. In this reasearch, the reasearch uses pluralism perspective to describe the role of Thaliban on increassing opium production in Afghanistan. This reasearch is supported by role theory. Liberalism concept is also provided to support this reasearch.Keyword : Opium Pruduction and trade, Taliban, Insurgency